Pemberdayaan Masyarakat Berbasis Pada Program Pemberdayaan Fakir Miskin (Studi Penelitian di Desa Mundak Jaya Kecamatan Cikedung Kabupaten Indramayu) - Aris Wanto; Purwoko .; Achmad Taufiq (Journal of Politic and Government Studies, 2014)
ABSTRACTPoverty is a phenomenon or a social phenomenon that is almost as old as the human civilization. In each area there is poverty in Indonesia name must always be there no matter how good the area is, because of poverty and well-being are like two sides of a coin that can not be liberated. Therefore, to address the problem of poverty that exist in Indramayu Regency, Regents and Local Government / agencies related to the problem of poverty has put together a strategy to address the problem of poverty in the district of Indramayu.Research approaches in Poor People Empowerment Program Year 2011 (Case Studies Business Group in the Village Mundak Jaya sub-district of Indramayu district Cikedung). This departs from the meaning of descriptive research approach itself, that an analytical descriptive method of gathering facts through the proper interpretation. This method is shown to study the issues that arise in the community in certain situations, including public relations, activities, attitudes, opinions, as well as ongoing processes and their effects on certain phenomena in the society.The fact shows that the implementation of the program in the field of KUBE FM in the village Mundak Jaya sub-district of Indramayu district Cikedung can not say success, is evident from the 8 (Eight) KUBE FM in the village Mundak Jaya. The program is now not active / running again, but the goats on the KUBE FM Desa Jaya Mundak from the year 2011 until now there are growing well and the goat, which is only 4 KUBE FM who still survive, thrive and breed goats that KUBE FM